Hubungan Pemberian Makanan Pendamping ASI (Mp-ASI) Dengan Status Gizi Pada Anak Usia 6-24 Bulan - Ayu Nina Mirania; Stephanie Lexy Louis (STIKES Citra Delima Bangka Belitung, 2021)
Under-five children with poor nutrition may suffer a decrease up to 10 percent in intelligence. It, in turn, may has some negative impact in form of deteriorating human resource quality. Age of 0-24 months is a critical period in children growth and development, given that it is during the time period where chidren are naturally growing most optimally both in intelligence and physically. The optimal growth can be realized if the children receive sufficient nutrient intakes. The purpose of the present research is to determine the relationship between giving foods as supplement to mother’s milk (MP-ASI) and the nutritional status of 6-24 month children. The research method was an analytical survey, with a cross sectional approach. The research sample was selected by using a total sampling technique. The data analysis technique used was chi squard test. With a Fisher alternative test. The research result revealed that there were two related variables, namely: Age where MP-ASI was given (p=0.000) and the frequency of giving MP-ASI (p=0.002) with 6-24 month children’s nutritional status by a relationship falling into a category of moderate, wheras MP-ASI texture (p=0.172) and MP-ASI type have no significant relationship. It was suggested for Puskesmas 11 Ilir to consistently convey information on the importance of paying attention to giving MP-ASI.